Characterisation of thiocyanate degradation in a mixed culture activated sludge process treating coke wastewater - Raper, Eleanor; Stephenson, Tom; Fisher, Raymond; Anderson, David R.; Soares, Ana (Elsevier, 2019)
Microbial degradation of thiocyanate (SCN−) has been reported to suffer from instability highlighting the need for improved understanding of underlying mechanisms and boundaries. Respirometry, batch tests and DNA sequencing analysis were used to improve understanding of a mixed culture treating coke wastewater rich in SCN−. An uncultured species of Thiobacillus was the most abundant species (26%) and displayed similar metabolic capabilities to Thiobacillus denitrificans and Thiobacillus thioparus. Thiocyanate was hydrolysed/oxidised to NH4+-N, HCO3− and SO42−. Nevertheless, at 360–2100 mg SCN−/L a breakdown in the degradation pathway was observed. Respirometry tests demonstrated that NH4+-N was inhibitory to SCN− degradation (IC50: 316 mg/L). Likewise, phenol (180 mg/L) and hydroxylamine (0.25–16 mg/L) reduced SCN− degradation by 41% and ca. 7%, respectively. The understanding of the SCN− degradation pathways can enable stable treatment efficiencies and compliance with effluent of <4 mg SCN/L, required by the Industrial Emissions Directive.
Keywords: Thiocyanate; Coke wastewater; Thiobacillus denitrificans; Thiobacillus thioparus